Integrative cognitive neuropsychological program emphasizing brain response to enhance inhibitory control among substance abusers at the alternative rehabilitation communities in Eastern Thailand - Haenjohn, Juthamas; Supwirapakorn, Warakorn; Namyen, Jatuporn (Frontiers in Psychiatry, 2025)
IntroductionInhibitory control (IC) deficit among substance abusers is a potential consequence of detrimental drug use and can also serve as a risk factor for drug-seeking behaviors, compromising substance abuse treatment and leading to drug relapse. This study examined the efficacy of an integrative cognitive neuropsychological program emphasizing brain response to enhance inhibitory control (ICNIC intervention program) among substance abusers.MethodsA total of 30 substance abusers were recruited and randomly assigned to either an ICNIC training group and a non-training control group. The ICNIC training group participated in a 12-session intervention program and a regular rehabilitative program at alternative treatment centers. The control group did not receive ICNIC training, but participated in only the regular rehabilitative program. IC was assessed using self-report measures and a cognitive performance task. Data were collected at three points: before ICNIC training, after ICNIC training, and at a 3-week follow-up ICNIC training. Statistical analyses were implemented.ResultsThe primary findings showed that substance abusers exhibited greater self-reported self-efficacy of behavioral IC after the ICNIC training, as assessed by the self-report measure, Behavioral Inhibitory Control Inventory – Substance Use (BICI-SU). There were no improvements in the ‘Go’ or ‘Stop’ trial accuracy (neither within-subject improvement nor between-group difference at the post-training or follow-up periods), and SSRT reaction time (neither pre- to post-training within-subject improvement nor between-group difference at post-training or follow-up periods), as measured by Stop Signal Substance Task (SSST). Moreover, the lack of improved accuracy coincided with slower responses to ‘Go’ stimuli in the ICNIC training group as compared to the non-training control group. Thus, the ICNIC training improved self-reported self-efficacy in IC and, therefore, may be associated with an improved and cautious response strategies for IC paradigms, resulting in slower response times. However, these strategies did not translate to improved response accuracy during the SSRT.ConclusionThe implementation of an ICNIC intervention program as a supplementary cognitive rehabilitation approach could potentially enhance self-efficacy of behavioral IC and improve response strategies among substance abusers. With further investigation, the program may be expected to contribute to an increase in cognitive control and promote behavioral changes that lead to positive therapeutic outcomes.